Una vaca o una gallina que se maten son pan para hoy pero hambre para mañana (Spain. Ministerio de Instrucción Pública. Dirección General de Bellas Artes, 1937)
Drawings of cow and chicken being slaughtered; on the bottom, drawings of bottles of milk, cheese, eggs Printed by the Associación de Obreros Litógrafos. Suggested translation: A cow or chicken that you kill may be food today, but hunger tomorrow PO-0105